EVALUASI PROGRAM PRAKTEK KERJA INDUSTRI DI SMK SARASWATI SALATIGA - Tarmidi Tarmidi; Bambang Ismanto (Universitas Pendidikan Ganesha, 2020)
Research at SMK Saraswati Salatiga was conducted to answer some questions: 1) How is the evaluation of the Prakerin context at SMK Saraswati Salatiga ?; 2) How is the evaluation of the Prakerin Input program at SMK Saraswati Salatiga?; 3) How is the evaluation process of the Prakerin program at SMK Saraswati Salatiga?; 4) how to evaluate products from Prakerin activities at SMK Saraswati Salatiga. This study uses the CIPP as a research method. Techniques used to collect data include, observation, interviews and documentation. Data evaluation used source triangulation methods and techniques. Data analysis techniques were carried out starting from the process of data collection, data reduction, data presentation, and variation that were presented in a descriptive qualitative manner. The results showed the vision and mission had been elaborated in the formulation of graduate competencies. Prakerin objectives have been implemented with breed, but there are still shortcomings. The formation of the Saraswati Vocational School Curriculum has involved the Industry. implementation techniques, student placement procedures, schedule and budget management are in accordance with established procedures. The implementation of the internship program has been carried out well, it's just that the monitoring of the supervising teacher needs to be improved. The products of the pre-program program show achievements in the good category, the benefits of the apprenticeship can be felt by all stekeholders ranging from industry, schools to students. For the evaluation of the apprenticeship activities already carried out, some are still lackingKeywords: Evaluation, Prakerin, CIPP